1998
DOI: 10.1007/s002310050249
|View full text |Cite
|
Sign up to set email alerts
|

Heat (mass) transfer between an impinging jet and a rotating disk

Abstract: The aim of this experimental study is to investigate the heat (mass) transfer of a rotating disk with an impinging circular jet. To facilitate the experiments, the naphthalene sublimation technique was employed. In order to analyze the results, measurements of the heat (mass) transfer of a stationary disk with an impinging jet and a rotating disk without jet impingement were also made. From the experimental results, it is found that the heat (mass) transfer are precisely divided into three regimes, namely the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 13 publications
2
26
0
Order By: Relevance
“…on rotational velocity, which confirms the observations of both Chen and Popiel [10,20]. The size of this area depends on the dimensionless spacing interval G, because it increases when G increases.…”
Section: Accepted Manuscriptsupporting
confidence: 88%
See 1 more Smart Citation
“…on rotational velocity, which confirms the observations of both Chen and Popiel [10,20]. The size of this area depends on the dimensionless spacing interval G, because it increases when G increases.…”
Section: Accepted Manuscriptsupporting
confidence: 88%
“…Other authors have studied mass and heat transfer changes in a single rotating disk configuration. Chen et al [10], Owen and Rogers [11] and Astarita [12] have examined the sensitivity of Nusselt numbers to jet diameter D, to the jet's Reynolds number Re j , and to the distance between the jet outlet and the disk e/D. In the case of a discoidal rotor-stator system without a jet impingement, the flow structure was also studied by few authors as Soong [13] or Poncet [14].…”
Section: Generalities About Rotating Disksmentioning
confidence: 99%
“…The impinging jet electrode configuration produces high local mass transfer rates [37]. The fluid dynamics and mass transfer characteristics of the impinging jet arrangement have been extensively studied [38][39][40].…”
Section: Techniques and Instrumentationmentioning
confidence: 99%
“…The technique of TLC was also used by Luo et al (2014) to explore the flow structure and heat transfer characteristics in a rotor-stator cavity with inlet at low radius. Chen et al (1998) experimentally investigated the heat transfer characteristics of a rotor disk with an impinging circular jet by the means of naphthalene sublimation, and found that the heat transfer can be divided into three regimes, namely the impingement dominated regime; the mixed regime and the rotation dominated regime.…”
Section: Heat Transfermentioning
confidence: 99%